The influence of UMKM service and product quality on tourist satisfaction - Manurung, Lambok; Ningsi, Etty Harya; Widodo, Slamet (International Journal of Applied Finance and Business Studies, 2025)
Tourist satisfaction is influenced not only by the attractions of a destination but also by the quality of services and products offered by local Micro, Small, and Medium Enterprises (MSMEs). However, limited attention has been given to how MSME performance affects tourist perceptions. This study aims to examine the influence of service quality and product quality of MSMEs on tourist satisfaction in several tourist destinations in North Sumatra, Indonesia. A quantitative research method was employed, using a survey approach with 150 respondents who had direct experience with local MSMEs. The data were analyzed using multiple regression analysis. The results indicate that both service quality and product quality have a significant positive effect on tourist satisfaction (p < 0.05), with a coefficient of determination (R²) of 0.68. These findings support the SERVQUAL and customer satisfaction theories, highlighting that modern tourists evaluate their travel experience not only through attractions but also through interactions with local businesses. The study recommends strengthening MSME capacity through improved service delivery, innovation of culture-based products, and the digitalization of marketing and transactions to enhance the competitiveness of tourism destinations.